IMPLEMENTASI BUDAYA RELIGIUS DALAM MEMBANGUN KARAKTER PESERTA DIDIK DI MADRASAH IBTIDAIYAH NU MAUDLU’UL ULUM PANDEAN KOTA MALANG - Chusnul May Syaroh; Muhammad Hanief; Muhammad Sulistiono (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
In this study was conducted to be able to know and describe how the implementation of culture in general and become an advantage applied in religious-based elementary schools, one of which is in Madrasah Ibtidaiyah NU Maudlu'ul Ulum Pandean Malang, which is related to efforts in building the religious character of learners through the application of religious culture madrasah. This research was conducted using observation data collection techniques, interviews, and documentation, this type of research uses case studies with qualitative approaches, using primary and secondary data sources, data analysis techniques of this study, namely data collection, data condensation, data presentation, conclusions and verification. Checking the validity of the findings of this study uses credibility through source triangulation techniques and techniques, dependability, and affirmability. In this case the researchers will discuss about religious culture, building the character of learners, and the implementation of madrasah religious culture in building the character of students in Madrasah ibtidaiyah NU Maudlu'ul Ulum Pandean Malang City.